A study to determine knowledge, attitudes and practices of diabetic patients towards their illness at UTH - Chiyengo,Mundanya N. (Lusaka: University of Zambia , School of Medicine, 2002)
The purpose of the studywas to determine the knowledge, attitudes and practices of diabetic clients towards their illness. The study was conducted from August to October 2001. The sample consisted of diabetic clients both male and female aged 10-50 years from various racial and socio economic backgrounds.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Nursing.
Includes bibliographical references.
Keywords: Diabetes; Diabetes Mellitus --therapy --Zambia.